Immunogenic Activity of Secreted Protein-Based Compounds Staphylococcus aureus № 6 - I. M. Gruber; E. A. Astashkina; O. V. Lebedinskaya; N. B. Egorova; M. V. Kiselevsky; F. V. Donenko; N. E. Yastrebova; O. M. Ignatova; E. A. Kurbatova; L. S. Cherkasova (Эпидемиология и вакцинопрофилактика)
Difficulties in the therapy of infection, caused by S. aureus, depends on the resistance of staphylococci to antibiotics, proceeding to chronicity of the diseases and the development on that background the depression of innate immunity functions and decreasing of the host resistance to the infection. In spite of tremendous efforts of researchers, up to date there are no commercial antistaphylococcal vaccine the efficacy of which would be proved in the completed clinical trials.Aim: obtaining secreted protein-based substances of the S. aureus № 6 and investigation their immunogenicity.Material and methods. Secreted protein-based substances (SPS) were obtain as: «initial» – from the filtrates of the culture fluid of the S. aureus № 6, grown to the end of the exponential phase according to the technology described previously [9], and I SPS and II SPS – after the ion-exchange chromatography of the «initial» SPS on the columns with Q-Sepharose and DEAE-Sepharose. The level of specific IgG antibodies in sera of immunized rabbits and mice determined in ELISA, the immunogenic activity evaluated in experiments of active and passive protection from the challenge performed on BALB/с mice and also by the determination of the bacterial content in organs and in the test of abscesses formation in kidneys. Results. Investigated SBS possessed the antigenic activity (the level of specific IgG antibodies in sera of immunized animals increased 2.2 – 7.5 times compared to the control groups), that is favor of the activation of the adaptive immunity system and significant protective activity revealed in experiments of active (index of efficacy 2.63 – 4.28) and passive protection. The immunization of mice with the «initial» and II SPS led to significant decrease of the number of colonyforming units of S. aureus and formation of abscesses in kidneys of mice. It is evidently, that investigated SPS, influence on the severity of staphylococcal infection and possesses the therapeutic effect.Conclusion. The preformed complex analysis at the current stage allowed to reveal perspectives of the further study of «initial» and II SPS in pre-clinical trials, as candidates, possessing the high protective facilities, for including them in the drug composition for immune prophylaxis and immunotherapy of diseases, caused by S. aureus.